Economic viability of cage-free system for commercial laying hens (Research, Society and Development, 2022)
With the growing concern of the food consumer market with animal welfare, the poultry sector, mainly in the production of eggs, is being forced to migrate to alternative production systems. In order to assist producers in making investment decisions, the objective was to carry out a case study and assess the economic feasibility of implementing a project for the creation of layers in the cage-free system, from the construction of the shed to the sale of eggs. For this, the costs for the construction of the installation (15m x 150m), acquisition of equipment and costs related to the production of eggs, from the purchase of the birds (15,750 birds of the Dekalb brown lineage), feed, vaccines, were carried out. between others. After analyzing the data, they were submitted to the application of financial indicators: net present value, internal rate of return, simple and discounted paybacks and the balance points: financial, accounting and economic. For the analyses, the proposed conditions were: 10% opportunity cost, 15% desired profit and time for investment recovery in a projected period of seven years. A simple payback of 4.25 and a composite of 5.8 years was obtained, net present value of R$ 141,504.37, which generated an internal rate of return of 14.33% and the percentages on sales were 49.38%; 35.92% and 90.46% for the accounting, financial and economic balance points respectively. It is concluded that, within what was proposed, the creation of layers in the cage-free system is financially viable.